2018
DOI: 10.1007/s11682-017-9787-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep white matter hyperintensities, microstructural integrity and dual task walking in older people

Abstract: To examine neural, physiological and cognitive influences on gait speed under single and dual-task conditions. Sixty-two community-dwelling older people (aged 80.0 ± 4.2 years) participated in our study. Gait speed was assessed with a timed 20-meter walk under single and dual-task (reciting alternate letters of the alphabet) conditions. Participants also underwent tests to estimate physiological fall risk based on five measures of sensorimotor function, cognitive function across five domains, brain white matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…8,9 This may be due to several mechanisms. 12 Finally, participation in physical activity improves muscular fitness 13 while it may be useful for maintaining neuronal health, 14 indicating that a person's lifestyle serves as a mediating factor to offset potential cognitive decline and physical frailty. 6 Second, white matter hyperintensities, which are a common neuropathological characteristic of MCI, 10 have been associated with greater cognitive 10 and muscular mass decline 11 and slowing of gait speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 This may be due to several mechanisms. 12 Finally, participation in physical activity improves muscular fitness 13 while it may be useful for maintaining neuronal health, 14 indicating that a person's lifestyle serves as a mediating factor to offset potential cognitive decline and physical frailty. 6 Second, white matter hyperintensities, which are a common neuropathological characteristic of MCI, 10 have been associated with greater cognitive 10 and muscular mass decline 11 and slowing of gait speed.…”
Section: Introductionmentioning
confidence: 99%
“…6 Second, white matter hyperintensities, which are a common neuropathological characteristic of MCI, 10 have been associated with greater cognitive 10 and muscular mass decline 11 and slowing of gait speed. 12 Finally, participation in physical activity improves muscular fitness 13 while it may be useful for maintaining neuronal health, 14 indicating that a person's lifestyle serves as a mediating factor to offset potential cognitive decline and physical frailty. From a public health and clinical perspective, the assessment of handgrip strength is of particular relevance as it is an objective measure of muscular fitness that is easily measurable at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Six temporal and spatial gait parameters were selected to identify associations with HRV indices, including “step time variability” and “step length variability” at preferred walking speed, as well as gait velocity under single- (ST) and dual-task (DT) conditions and at preferred and fast walking speeds: “velocity preferred-ST,” “velocity fast-ST,” “velocity preferred-DT,” and “velocity fast-DT.” The parameters were chosen based on findings, which have demonstrated their relation to brain functional or structural aspects (Tian et al, 2017 ; Ghanavati et al, 2018 ; Lucas et al, 2018 ). The GAITRite electronic walkway (CIR Systems, Havertown, PA, USA) with Platinum Version 4.0 software was used to assess gait parameters.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon can be explained by WMH in different locations that are associated with white matter damage on different fibers. Further studies found that FA changes in the anterior thalamus radiata, corpus callosum, and cingulum are related to impaired executive functions in patients with cerebral small vessel disease (Bender, Völkle, & Raz, ; Ghanavati et al, ; Johnson et al, ; Papma et al, ; Tuladhar et al, ). Based on these findings, it has been proposed that slower processing speeds caused by WMH are a result of “disconnection,” arguing that disrupted fiber integrity slows information flow among different brain regions, leading to brain activity alterations.…”
Section: Introductionmentioning
confidence: 99%